Vapour phase Guerbet condensation of ethanol to 1-butanol on CsX zeolite - Patrylak, Lyubov K.; Pertko, Olexandra P.; Valihura, Karina V.; Voloshyna, Yulia G. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2023)
Nowadays, the conversion of ethanol into valuable chemical products is getting wider application.One of such promising processes is Guerbet condensation of alcohols, which permits the obtaining of 1-butanol from renewable raw materials that are alternatives to petroleum ones.Oxide systems combining acid and basic sites in their composition are promising catalysts for such a transformation.In this study, the efficiency of the magnesium-aluminum oxide and zirconium-oxide catalysts was compared to the activity of the cesium form of X-type zeolite produced by hydrothermal ion exchange in the condensation of ethanol to 1-butanol. The integrity of the zeolite structure was confirmed by using the XRD and XRF analysis, as well as by the IR spectroscopy.The depth of exchange of native sodium for cesium was 82%. It was also found that cesium cations are localized only in ion-exchange positions of faujasite, in places SIII (supercages) and SI` (sodalite cages). CsX zeolite acid to basic sites ratio was found tobe close to optimal for this reaction. Cesium-containing zeolite at 300 °C showsethanol 35-55 % conversion and 20-25 % selectivity for 1-butanol, which is higher than the same characteristics for zirconium samples, but slightly inferior to magnesium-aluminum oxide catalysts. The obtained results indicate the promising use of zeolites of a similar nature in the process of condensation of ethanol to 1-butanol.